Modern problems of management in the sports field - Leonova Yuliia; Tеtіana Dorofieieva (Kharkiv State Academy of Physical Culture, 2019)
The purpose of work: to identify and describe modern problems of management in the domestic sports sphere. Material and methods of research: theoretical and practical researches of domestic scientists, scientific literature; methods of comparison, synthesis, analysis. Results: it was found that domestic legislation needed to be improved to effectively address the problems identified; create a special group of professionals who have recently acquired practical experience in the management and legal regulation of professional sports; reorient the system from facility maintenance to people development. Conclusions: the main problems of management in the domestic sports sphere were identified and described. The directions of effective solution of the identified problems were also mentioned.